Evolution of stress and magnetism during the first-order phase transition of MnAs/GaAs(001) - Ney, A; Das, A; Pampuch, C; Hesjedal, T; Kastner, M; Daweritz, L; Koch, R; Ploog, K (2004)
We have investigated epitaxial MnAs/GaAs(0 0 1) films in the phase transition region between 10°C and 40°C where hexagonal, ferromagnetic α-MnAs and paramagnetic, orthorhomic β-MnAs coexist. Quantitative stress measurements with a cantilever beam magnetometer reveal that during the phase transition the atomic distances change only in the vertical direction providing insight into the nature of the exchange coupling mechanism. © 2003 Elsevier B.V. All rights reserved.